Rett syndrome: Establishing a novel outcome measure for walking activity in an era of clinical trials for rare disorders - Downs, Jennepher; Leonard, H.; Jacoby, P.; Brisco, L.; Baikie, G.; Hill, Kylie (Taylor and Francis Ltd, 2015)
Background: Rett syndrome is a pervasive neurological disorder with impaired gait as one criterion. This study investigated the capacity of three accelerometer-type devices to measure walking activity in Rett syndrome. Methods: Twenty-six participants (mean 18 years, SD 8) wore an Actigraph, ActivPAL and StepWatch Activity Monitor (SAM) during a video-taped session of activities. Agreement was determined between step-counts derived from each accelerometer and observation. Repeatability of SAM-derived step counts was determined using pairs of one-minute epochs during which the same participant was observed to walk with the same cadence. Results: The mean difference (limit of agreement) for the Actigraph, ActivPAL and SAM were −41 (SD 33), −16 (SD 21) and −1 (SD 16) steps/min, respectively. Agreement was influenced by a device/cadence interaction (p < 0.001) with greater under-recording at higher cadences. For SAM data, repeatability of step-count pairs was excellent (intraclass correlation coefficient 0.91, 95% CI 0.79–0.96). The standard error of measurement was 6 steps/min and we would be 95% confident that a change ≥17 steps/min would be greater than within-subject measurement error. Conclusions: The capacity of the SAM to measure physical activity in Rett syndrome allows focus on participation-based activities in clinical practice and clinical trials.